Assessment of the marginal fit, ceramo-metal shear bond strength and the fractographic analysis of sinter cast gold: An In-vitro study - Hetal Turakhia; Sabita M Ram; Aruna Mehta; Abhishek S Nayyar (Wolters Kluwer Medknow Publications, 2018)
Introduction: The fractographic analysis is performed by observing, measuring, and interpreting the fracture surface topography that can determine many features of the microstructure of materials and the mechanics of the fracture. The aim of this study was to assess the marginal fit and the ceramo-metal shear bond strength of sinter cast gold, and to analyze the debonded sample by fractography. Materials and Methods: A total of five sinter cast gold copings were prepared on a stainless master die resembling a maxillary 1st pre-molar to receive a ceramo-metal restoration. Each of the copings was then assessed for the marginal fit before and after ceramic firing. In addition, a total of five ceramo-metal discs were fabricated for testing shear bond strength at the metal-ceramic interface. The samples were subjected to increasing shear load on a universal testing machine with crosshead speed of 0.002 mm/s. The load at which the samples debonded completely was noted, and the fractographic analysis of the samples was performed. Results: The mean marginal fit found in this study for sinter cast gold before ceramic firing was found to be 11.5 μm with a standard deviation of ±4.64 μm, and after ceramic firing, it was found to be 9.38 μm with a standard deviation of ±3.57 μm. The average shear bond strength at the sinter cast gold ceramic interface was 18.216 MPa. The fractographic analysis showed the globular microstructure of sinter cast gold on sintering, adhesive, and mix-mode type of fracture with the presence of both gold and ceramic. Conclusion: The marginal fit observed before and after ceramic firing was within clinically acceptable range, whereas the ceramo-metal shear bond strength between sinter cast gold and ceramic was found to be inadequate.